Influence of Retirement on Adherence to Statins in the Insurance Medicine All-Sweden Total Population Data Base. - Heli Halava; Hugo Westerlund; Maarit Jaana Korhonen; Jaana Pentti; Mika Kivimäki; Linnea Kjeldgård; Kristina Alexanderson; Jussi Vahtera (PLoS ONE)
Background Retirement has been suggested to reduce medication adherence, but no evidence is available for statins. We investigated changes in adherence to statins among Swedish adults after retirement. Methods A prospective cohort study was carried out on all individuals living in Sweden on 31 December 2004, alive in 2010, having purchased statins in the second half of 2005, and retired in 2008 (n=11 718). We used prescription dispensing data in 2006-2010 to determine nonadherence (defined as <80% of days covered by filled prescriptions) before and after old-age or disability retirement. Using multiple repeat measurements of filled statin prescriptions, we calculated the annual prevalence rates of nonadherence for those who continued therapy. Discontinuation was defined as no statin dispensations during a calendar year. Results After adjustment for age at retirement, the prevalence ratio (PR) of nonadherence after retirement in comparison with those before retirement was 1.23 [95% confidence interval (CI) 1.17-1.29] for the men and 1.19 (95% CI 1.13-1.26) for the women. A post-retirement increase in nonadherence was consistently observed across the strata of age at retirement, marital status, education, income, type of retirement, and participants with and without cardiovascular disease, the largest increases being observed for statin use in secondary prevention (men: PR 1.38, 95% CI 1.26-1.54; women: PR 1.43, 1.18-1.72). For primary prevention, the corresponding prevalence ratios were 1.18 (95% CI 1.13‒1.25) and 1.18 (95% CI 1.11-1.24), respectively. Interpretation Retirement appears to be associated with increased nonadherence to statin therapy among Swedish men and women.